Avatar-оriented management of organizations as a new direction of management - Tsarelnyk, Dmytro (Актуальні питання економічних наук, 2025)
The study is motivated by the transformation of management systems under the influence of digitalization, the development of artificial intelligence, and the spread of platform-based organizational models, which necessitates the formation of new management approaches capable of ensuring effective coordination, data processing, and decision-making in complex digital environments. The growing role of digital representations of subjects and processes actualizes the need for scientific substantiation of avatar-oriented management as an independent direction of management. The purpose of the article is to theoretically substantiate avatar-oriented management of organizations as a new direction of management and to determine its impact on improving the efficiency of management processes in a digital environment. The research methods are based on the use of system analysis, generalization and systematization of scientific approaches, as well as logical-analytical methods for studying the functioning of avatar-based models in management systems. As a result of the study, the essence and conceptual foundations of avatar-oriented management have been explored, the functional roles of avatars in ensuring coordination, control, and communication have been identified, and approaches to their integration into organizational structures and digital platforms have been generalized. It has been revealed that the use of avatar representations contributes to increased transparency of activities, reduction of time lags in decision-making, and the transition to proactive management. The main implementation problems have been identified, including methodological uncertainty, data quality issues, integration limitations, as well as organizational and security challenges. It has been proven that the effective application of avatar-oriented approaches requires standardization of digital models, ensuring consistency of information flows, integration with corporate systems, and the development of analytical decision-support tools. The conclusions indicate that avatar-oriented management forms a new management paradigm that enhances adaptability, coordination, and overall organizational performance in digital environments. Further research should focus on the development of quantitative models for evaluating effectiveness, integration with artificial intelligence technologies, and the study of security and ethical aspects of digital representations.